(untitled) (Journal of Plant Disease Sciences, 2023)
Anthracnose, or fruit rot disease, caused by Colletotrichum capsici (Syd.) Butler and Bisby, is one of the most devastating and perplexing chilli diseases, causing significant quantitative and qualitative losses to the crop. During the studies on chilli anthracnose caused by Colletotrichum capsici, experiments were carried out to isolate the pathogen, identify it based on cultural and morphological characteristics, as well as microscopic observations, and demonstrate its pathogenicity on susceptible chilli varieties in sterilized pots. Furthermore, various culture medias, including potato dextrose agar, oat meal agar, Richard’s agar, Czapek’s dox agar, corn meal agar, yeast extract agar, and yeast mannitol agar, were tested to determine which media is best for growing the pathogen Colletotrichum capsici. Colletotrichum capsici radial mycelial growth was investigated In vitro across all culture mediums. All of the media tested promoted the growth of the test pathogen. The results showed that, of the seven culture medias examined, potato dextrose agar was the most suited and promoted the most radial mycelial development (89.21 mm). The second-best was oat meal agar (81.75 mm), followed by Richard’s agar (68.45 mm) for radial mycelial growth.